Influence of intermediate stiffeners on the axial capacity of cold-formed steel back-to-back built-up unequal angle sections. (August 2021) - Ananthi, G. Beulah Gnana; Deepak, M.S.; Roy, Krishanu; Lim, James B.P.
Abstract: In Cold-formed steel (CFS) structures, such as trusses, transmission towers and portal frames, the use of back-to-back built-up CFS unequal angle sections are becoming increasingly popular. In such an arrangement, screw fasteners are required at discrete points along the length to prevent the unequal angle-sections from buckling independently. No research has been reported in the literature which investigated the influence of stiffeners on axial capacity of back-to-back built-up CFS T shaped angle section columns (BUATC). The issue is addressed herein. This paper presents a total of 77 new results comprising 13 axial compression tests and 64 finite element analysis (FEA) results on axial capacity of BUATC with and without intermediate stiffeners. From the experimental results, it was found that for the case of BUATC with two stiffeners in the longer leg and one stiffener in the shorter leg, the axial capacity was increased by 20% on average, when compared to the axial capacity of built-up angles without any intermediate stiffener. A nonlinear finite element (FE) model is then described, which includes material non-linearity and geometric imperfections. The FE model was validated against the experimental test results, which showed good agreement, both in terms of failure load and deformed shape at failure. The validated FE model was used to conduct a parametric study to investigate the effect of stiffeners on axial strength of BUATC. Two different cross sections and two different lengths (stub and short columns) were considered in the parametric study. Axial strengths obtained from the experimental tests and FE analyses were used to assess the performance of the current design guidelines as per the Direct Strength Method (DSM); obtained comparisons show that the current DSM is reliable and conservative by 14% on average.